Water demand and consumption, and willingness to pay to conserve Tigum-Aganan watershed for sustainable water supply a household survey in Iloilo City Proper - Colacion, Gwin Carlo S
This study examines the different sources of water that households used, its different prices and the uses of water for the households in relation to their water demand and consumption. This study also determined the respondents' willingnes to contribute an amount for the Tigum-Aganan Watershed Conservation., A stratified random sampling of 174 respondents across 10 selected barangays of Iloilo City Proper was conducted. Respondents were then interviewed to get the data needed for the study. The research showed on the average respondents ' were 44.62 years old, had 10.17 number of years in education corresponding to high school graduate level, had an average annual income of 200,287.36 pesos, household size of 6.21, and 2.32 number gainfully employed in the family. Water consumption was purified water, MIWD water, deep well, and delivered water that had various uses like drinking, cooking, bathing, cleaning, laundry and gardening. Water quality and its corresponding uses are very important for the respondents in choosing their water sources. Purified water was the most expensive on the other hand deep well was almost free. It should be emphasized that there was an installation cost but as water withdrawn increases installation cost decreases, thus diminishing the price per unit. Of the total 174 respondents 99.93 were willing to pay for the conservation the Tigum-Aganan watershed. Their main reason was they want a reliable supply of water. Those were not willing to pay cited their lack of trust on the government as their dominant reason for such.